Life Insurance Awareness Levels among College Students in Bharatpur: An Exploratory Study - Pokharel, Sunil (BIC Journal of Management, 2025)
This exploratory research aims to investigate the level of awareness that college students in Bharatpur Metropolitan City, Chitwan, Nepal, have regarding life insurance policies. Life protection can be a simple yet effective financial tool that brings security and peace of mind, but it is often underutilized among younger individuals. Assessing the Awareness level and significant perspectives of college students can be beneficial in developing offerings from insurers to meet the needs of this population. This research employed a mixed-methods approach to collect data from a sample of college students, combining surveys with qualitative interviews for the study conducted in 2025. The study is based on random sample techniques, using 294 respondents from Bharatpur. According to the study, 63 percent of respondents believe that having life insurance is important, 35 percent believe it is mandatory, and 2 percent do not see the need to consider it. The survey also revealed that 56 percent of college students who plan to get life insurance in the future would want to reduce the likelihood of an economic disaster brought on by unforeseen future events.